Genetic Dissection and Quantitative Trait Loci Mapping of Agronomic and Fodder Quality Traits in Sorghum Under Different Water Regimes - Somegowda, Vinutha K.; Prasad, Kodukula V. S. V.; Naravula, Jalaja; Vemula, Anilkumar; Selvanayagam, Sivasubramani; Rathore, Abhishek; Jones, Chris S.; Gupta, Rajeev; Deshpande, Santosh P. (Frontiers in Plant Science, 2022)
Livestock is an additional source of income for marginal farmers, but crop residue used as feed reduces the livestock product yield and quality, due to low digestibility and nitrogen content in crop residue. The key trait to determine the quality of feed is digestibility (IVOMD - in vitro digestibility) as it influences the cost of feed. Sorghum breeding can be directed to achieve genetic gain for biomass and digestibility without any trade-off. The mean comparison has shown significant difference for biomass under control (4.82 and 5.82) and stress (8.71 and 43.83) in two years and IVOMD was significant under control treatment (24.04 and 2.71) but stress shown no significant difference for IVOMD in both years. Agronomic and fodder quality (key- nitrogen and digestibility) were found to have significant differences across treatments within and across years for the population. Dry biomass yield has significant σg2 (13035 in 2016 and 3395 in 2017) and σgxt2 (5471 in 2016 and 2057 in 2017) while IVOMD showed significant difference under control σg2 (0.253 in 2016) and σgxt2 (0.148 in 2017). The correlation study shows no relation between biomass and digestibility traits under control (0.03) but had significant positive relation under stress (0.24). However, negative relation was observed between digestibility and grain yield (-0.16) under control and no significant relation was observed under stress. QTL dissection helps to identify the genomic regions for high biomass and digestibility. The population was genotyped using GBS and SNP was called under version 3.1, after filtering for MAF (0.1% with 90% coverage) gave 1141 markers. A linkage map was constructed using the QTL IciMapping Version 4.2.53 with additive and epistatic model. A total of 294 QTL were detected with 534 epistatic interactions for all traits. Agronomic traits like fresh and dry weight along with plant height was mapped on LG7 while IVOMD was mapped on LG1, 2 and 8. These QTL were annotated to previous reported genes and are closely related to many significant genes that are playing role in nitrogen metabolism and cell wall related functions.